Income analysis of beef and racing cattle farmers in Sapudi Island Regency of Sumenep - . Rizqina; L. Jannah; . Isbandi; E. Rianto; S. I. Santoso (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2011)
The purpose of this study was to assess the farmer income with bussiness scale 2-3 cattle or 4-6 cattle on-farm beef cattle and racing bull in the Sapudi island. The respondents consisted of 26 beef cattle farmers and 26 racing cattle farmers from the sub district Nonggunong and sub district Gayam, island of Sapudi of Sumenep Regency. Primary data was obtained through interviewing with the farmers based questionnaire prepared before hand, covering farmer identity, business investment component of livestock, livestock business costs (fixed costs and variable costs), revenues and expenditures cattle business. The data were analyzed using analysis of B/C ratio, BEP of price and BEP of production on each of farmers and their respective number of cattle raising. Bussiness scale was categorized according to the number of cattle raised by the farmers, namely those having 2-3 either beef or racing cattle = 2-3 scale, those having 4-5 cattle= 4-5 scale and those having 4-6 racing cattle= 4-6 scale. For beef cattle business, up to bussiness scale 4-5 was still not profitable but for racing cattle farmers, bussiness scale of 4-6 cattle was more profitable than those with bussiness scale 2-3 cattle.